2010
DOI: 10.2320/matertrans.m2009361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Current Density and Organic Additives on the Texture and Hardness of Ni Electrodeposited from Sulfamate and Watt’s Solutions

Abstract: Ni electrodeposition was galvanostatically conducted over the current density range 500-2000 A/m 2 in unagitated sulfamate and Watt's solutions at 323 and 313 K, respectively, to examine the effect of current density and organic additives on the texture, crystal orientation, and hardness of the deposited Ni. The overpotential for Ni deposition increased by the addition of polyethylene glycol (PEG) or saccharin in both sulfamate and Watt's solutions. The degree of increase in the overpotential in a PEG-containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…8) Previously, authors have reported the effect of current density and organic additives on the texture, crystal orientation, and hardness of the Ni deposited from sulfamate and Watt's solutions. 9,10) The hardness of the deposited Ni increases with the addition of organic additives. Although the increase in hardness of the deposited Ni with organic additives seems to be due to both the co-deposition of the additives and a decrease in the particle size of Ni, there have been very few studies on the effect of the additive content on the texture and hardness of the deposited Ni.…”
Section: Introductionmentioning
confidence: 99%
“…8) Previously, authors have reported the effect of current density and organic additives on the texture, crystal orientation, and hardness of the Ni deposited from sulfamate and Watt's solutions. 9,10) The hardness of the deposited Ni increases with the addition of organic additives. Although the increase in hardness of the deposited Ni with organic additives seems to be due to both the co-deposition of the additives and a decrease in the particle size of Ni, there have been very few studies on the effect of the additive content on the texture and hardness of the deposited Ni.…”
Section: Introductionmentioning
confidence: 99%